Conceptualizing, measuring and evaluating constructs of the adolescent neighbourhood social environment: A systematic review. (December 2017) - Martin, Gina; Gavine, Anna; Inchley, Joanna; Currie, Candace
Abstract: Interest in the effects of neighbourhood social dimensions on adolescent health and well-being has recently increased. A number of measures have been used in studies of adolescents' neighbourhood social environments yet no consensus exists on how these measures are conceptualised or operationalised. To better understand associations between the neighbourhood social environment and adolescent outcomes, reliable and valid measures are required. Accordingly, this paper presents findings from a systematic review of instruments used to measure adolescents' neighbourhood social environment. Searches were conducted across six databases (Medline, Scopus, Applied Social Science Index and Abstracts, Cumulative Index to Nursing and Allied Health Literature, Web of Science, and PsycInfo) to identify studies that measured adolescents' perspectives of their neighbourhood social environment. Quality assessment was conducted using a modified version of the Consensus-based Standards for the selection of health Measurement Instruments and studies were excluded on the basis of quality of the reporting. Items and constructs were coded thematically to better understand the original conceptualisation. Out of 13, 689 unique articles screened, 205 reported on measures of the adolescent neighbourhood social environment and 32 (with a total of 56 measures) met the required level of reporting quality and were included in a narrative synthesis. There was considerable heterogeneity in both the conceptualisations and the items used in measuring adolescent neighbourhood social environmental constructs. Only one construct, neighbourhood social control, was deemed distinct from other concepts. Constructs of disorder and safety also appeared distinct from constructs such as support, cohesion, and attachment/sense of community and belonging which use a high proportion of measures that deal with relationships and ties within the community. Based on these findings we recommend refined conceptualisation and improved transparency in the reporting of measures in order to promote comparability of studies and move the field forward.